HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP SELF-ESTEEM ANAK USIA 5-6 TAHUN - Jessica Felicia Faustina (Indonesian Journal of Education and Learning, 2019)
Socio-economic status of the elderly is the seat of the family in society, self-esteem is a picture of myself to hang out with the neighborhood to have a confident, independent attitude. This research aims to find out: 1) if there is a relationship between socio-economic status of the elderly against self-esteem children ages 5-6 years; 2) how the relationship between socio-economic status of the elderly against self-esteem children aged 5-6 years. The design of this study using sequential explanatory design. Participants in the study are a group of B-3 X TK Puwakarta that add up to 24 children and the elderly. Data collection techniques using question form, observation, and documentation. Data analysis in this study uses two meteode research kuantitaif further qualitative analytical techniques descriptive statistics and correlation of analissi engineering product moment correlation test hypotheses of social economic status of the elderly against self-esteem. The results of this research are: 1) there was no relationship between socio-economic status of the elderly against self-esteem children ages 5-6 years since rxy (24) =-0.036 rxy < 0.2 this indicates that there is a negative relationship between socio-economic status of the elderly with self-esteem; 2) socio-economic status of the elderly do not touch against the self-esteem children ages 5-6 years 5-6 years of age because the child has low self-esteem and high self arises from a child because looking at him to be able to have a confident, independent, and spirit learn.Key Words: Socio-Economic Status Of Parents, Self-esteem